Factors leading to interpersonal relationship with pengkid/butch: femme women role player perspective - Ab Aziz, Alice Nurizza; Abdul Rahman, Abdul Razak; Wan Jaafar, Wan Munira; Adam Assim, Mohd Ibrani Shahrimin (Human Resource Management Academic Research Society, 2019)
The phenomena of homosexual relationship have become common challenging Malaysian status as an Islamic nation, called for a serious attention. This behavior needs to curbed to ensure that such homosexual relationship be arrested comprehensively and practically with widespread specific on this issues. However, most studies focus on “Pengkid/Butch” which is a female lesbian as a “male role player” and the” female role player”, “femme”, which is actually a lesbian women, maintaining their female characteristics and partnered with the “Pengkid” or “Butch”, In view of that, the focus specifically to the female femme which involved actively in interpersonal relationship “game play” as it is seen as overlooked by community compared to Pengkid as a dominant character. In order to acquire in depth information and understanding, semi structured interview has been designed and 10 of Malays Muslims respondents within Federal Territory, Kuala Lumpur and Selangor have been interviewed. Results of shown that the Femme group is active and the driven factor in the interpersonal relationship attributed by 6 main factors. Resultant of this revealed that interpersonal relationship is stronger ever though, the satisfaction and orgasm is limited and against the natural human biological and sexual desires. This provides a new frontier of understanding from the femme behavioral perspective and recommended that an appropriate criteria/methodology to arrest as well social support be thought of to render help to this group of community.